We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
-1
193
1
avatar+1206 

Let f(x)=3x+4 and g(x)=2x-3. If h(x)=f(g(x)), then what is the inverse of h(x)?

 Jul 21, 2018
 #1
avatar+102383 
+1

Let f(x)=3x+4 and g(x)=2x-3. If h(x)=f(g(x)), then what is the inverse of h(x)?

 

f(g(x))  means to put the function g  into  f

 

h(x)  = f(g(x))  = 3 [ 2x - 3 ]  + 4   =   6x - 9 + 4  =  6x - 5

 

So

 

h(x)  = 6x  - 5      for  h(x), write y

 

y  = 6x  - 5        we want to get x by itself...add 5 to both sides

 

y + 5  = 6x       divide both sides by  6

 

[ y + 5 ] / 6    = x         "swap" x and y

 

[ x + 5 ] / 6  = y      and this is the inverse of  h

 

 

cool cool cool

 Jul 21, 2018

25 Online Users

avatar